Proceedings of the 13th International Conference on Multimodal Interfaces 2011
DOI: 10.1145/2070481.2070558
|View full text |Cite
|
Sign up to set email alerts
|

Temporal binding of multimodal controls for dynamic map displays

Abstract: Dynamic map displays are visual interfaces that show the spatial positions of objects of interest (e.g., people, robots, vehicles), and can be updated with user commands as well as world changes, often in real time. Multimodal (speech and touch) controls were designed for a U.S. Army Research Laboratory dynamic map display to allow users to provide supervisory control of a simulated robotic swarm. This study characterized the effects of user performance (input difficulty, modality preference, and response to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The overall consistencies are much lower (82.9%) and show a more divergent characteristic per user than reported in [7,9]. The same holds for another user classification based on the order of inputs [1,2,5]. None of these simple measures showed enough consistency, that promising error detection, based on them, could be expected.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The overall consistencies are much lower (82.9%) and show a more divergent characteristic per user than reported in [7,9]. The same holds for another user classification based on the order of inputs [1,2,5]. None of these simple measures showed enough consistency, that promising error detection, based on them, could be expected.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast to the findings of Oviatt et al, where typically simultaneous integration patterns were much more often observed, here, all of the inputs were sequential ones. Haas et al [2] conclude that this may be due to the fact, that their tasks involved much shorter (command-like) speech inputs than those of Oviatt et al…”
Section: Related Workmentioning
confidence: 97%
See 3 more Smart Citations